NLRP1 gene polymorphism rs2670660 is associated with vitiligo in the Pakistani population - Sehresh Murtaza; Nasir Masood; Maleeha Azam; Muhammad Ajmal (Molecular Biology Reports, 2026)

Genomic characterization of genes controlling stay-green trait in bread wheat - Alia Anwar; Xingguo Ye; Hafiz Sabah-Ud-Din Mazhar; Muhammad Waleed Meeran; Ralf Müller-Xing; Muhammad Ashfaq; Muhammad Arshad Javed; Javaria Tabassum; Umar Masood Quraishi; Farheen Solangi; Shajiha Naeem (Euphytica, 2026)

Nano-formulated β-glucans from Saccharomyces cerevisiae enhance immunity and protection against coccidiosis in broiler chickens - Muhammad Noor; Muhammad Irfan Anwar; Mian Muhammad Awais; Masood Akhtar; Faqir Muhammad (Veterinary Parasitology, 2026)

Enhancement of enzyme-induced carbonate precipitation (EICP) for sustainable soil stabilization in loess slopes using soybean-derived urease and organic nucleating agents - Dequan Kong; Muhammad Muneer; Rong Wan; Xinyang Liu; Masood ur Rahman; Shihao Gu; Mouhong Wang (Engineering Geology, 2026)

Molecular target for neuroinflammation and pain management: transient receptor potential vanilloid 1 - Zunera Chauhdary; Muhammad Saad Masood; Muhammad Irfan; Amina Shafi; Duryab Rafique; Abeesha Arif; Maryam Akmal (Inflammopharmacology, 2026)

Polybrominated diphenyl ethers (PBDEs) contamination across environmental compartments in Europe - Khaled Abass; Lucy Semerjian; Petra Roupcová; Jana Stamenovic; Muhammad A. Masood; Minashree Kumari; Paul Botwe; Jana Suchanková; Kateřina Sikorová; Izabela Šudrychová; Lenka Klimková; Dana Chudová (Environmental Research, 2026)

Retraction notice to ‘Hispolon: A natural polyphenol and emerging cancer killer by multiple cellular signaling pathways’ [Environ. Res. 190 (2020) 110017] - Ayesha Sarfraz; Azhar Rasul; Iqra Sarfraz; Muhammad Ajmal Shah; Ghulam Hussain; Nusrat Shafiq; Muqaddas Masood; Şevki Adem; Satyajit D. Sarker; Xiaomeng Li (Environmental Research, 2026)

Transport of buoyant microplastics in natural soils under rainfall or irrigation conditions - Muhammad Masood Ashiq; Peyman Babakhani; Brian Waldron; Maryam Salehi; Kati Bell; Farhad Jazaei (ENGINEERING Environment, 2026)
Microplastics (MPs) pose a significant threat to soil and groundwater quality. Yet, investigating their transport in soils has so far been limited to conventional packed column experiments where particles suspended in a stock dispersion are injected from one side of the column. This, however, does not represent the natural condition where buoyant MPs are released on the surface of the soil and storm or irrigation water induces their penetration into the soil depth. To consider such prevailing natural condition, we develop a new column experiment setup and a corresponding modeling approach to study the transport of low-density polyethylene MPs in different farmland soil types and investigate the impact of photodegradation and natural organic matter. Results revealed a substantial penetration of buoyant MPs in the soil due to the irrigation or rainfall scenarios. Mathematical modeling showed that processes such as attachment, detachment, blocking, and straining, previously observed for colloidal particles in direct injection scenarios, occur for buoyant MPs irrigation or rainfall release scenario. MPs transport increased in silt compared to the silt loam and in the presence of natural organic matter. UV-photodegraded MPs transport was greater than pristine MPs because of increased surface charge and electrostatic repulsion, reducing MPs attachment to soil.

Chronic ischemic heart disease and co-recorded depression on death certificates: national mortality trends in the United States - Sarim Hassan Shahab; Muhammad Uzair Afzal; Kanza Zainab; Esha Umair; Hadia Ghazala Masood; Umer Abdur Rahman (Next Research, 2026)

Melatonin and melatonin-functionalized quantum dots enhance antioxidant defense, attenuate cadmium uptake, and improve yield performance in bread wheat under cadmium stress - Shiza Mukhtar; Samina Bibi; Muhammad Anas; Munaza Mehreen; Umar Masood Quraishi (Biocatalysis and Agricultural Biotechnology, 2026)

Salicylic Acid and Proline-Functionalized Carbon Quantum Dots Mitigate Nickel Toxicity in Wheat by Enhancing Antioxidant Defense, Metal Homeostasis, and Nutritional Quality - Syed Abu Bakr Haider Bukhari; Minhas Elahi; Muhammad Anas; Shoaib Abbas; Waseem Ahmed Khattak; Umar Masood Quraishi (Journal of Plant Growth Regulation, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes” [Fuel 412 (2025) 138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Whole Genome Analysis of Propiconazole-Degrading Serratia marcescens BM-Q: A Rhizobacterium - Maha Binte Masood; Muhammad Nadeem Hassan (Current Microbiology, 2026)

Prevalence of Vitamin D Deficiency in Ataxia-Telangiectasia: A Systematic Review and Single Arm Meta-Analysis - Muhammad Junaid Iqbal; Muteeba Azhar; Hammad Javaid; Amina Hassan; Ayesha Masood; Michele Menotta (The Cerebellum, 2026)

Clinical evaluation of adjunctive magnesium therapy in patients receiving antidepressants for depression—open label, nonrandomized clinical trial - Afifa Siddique; Uzma Naeem; Muhammad Masood Khokhar; Mushayada Irshad; Tayaba Farooq; Sughra Kanwal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Removal of arsenic from aqueous solution using a surface-functionalized magnetic biochar derived from Chlorella - Muhammad Irfan; Israr Masood ul Hasan; Muhammad Jafir; Chang Li; Jie Hu; Muhammad Moeen ud din; Khalid Hussain; Yixing Zhu; Liugen Zheng (Marine Pollution Bulletin, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes”. [Fuel 412 (2025) 138022. doi: 10.1016/j.fuel.2025.138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Polybrominated diphenyl ethers (PBDEs) contaminations across environmental compartments in the Middle East and North Africa - Khaled Abass; Jana Stamenovic; Muhammad A. Masood; Minashree Kumari; Abdallah Shanableh; Lucy Semerjian (Environmental Research, 2026)

Serratia marcescens Isolated from the Cereals of Multi-Copping Systems Mitigate Drought Stress in Wheat (Triticum aestivum. L.) - Madiha Shoukat; Maha binte Masood; Pari Wash; Muhammad Nadeem Hassan (Journal of Crop Health, 2026)

Unearthing profits: The impact of ripping depth on cost-benefit dynamics in south-eastern Australia's sandy soils - Muhammad Masood Azeem; Therese McBeath; Jackie Ouzman; Chris Saunders; Rick Llewellyn (Soil and Tillage Research, 2026)

Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Assessment of temporal and spatial shifts in climatic parameters and their impact on crop water requirement in the Lower Chenab Canal Command Area, Pakistan - Ahtisham Mehmood; Muhammad Masood; Ahmad Mujtaba; Ghulam Nabi; Abu Bakar Arshed (Theoretical and Applied Climatology, 2026)

A scalable framework for flash flood hazard assessment in data-scarce catchments using coupled modeling - Moiz Ahmed Khan; Muhammad Masood; Mudassar Iqbal; Saliha Qamar; Muhammad Awais Zafar; Khalil Ahmad (Modeling Earth Systems and Environment, 2026)

Retraction Note: Optimizing callogenesis in five potential medicinal herbs for the bioactive constituents: a sustainable approach to pharmaceutical production - Muhammad Wasim Haider; Muhammad Nafees; Maryyam Bint-e-Tariq; Umar Farooq; Tanveer Hussain; Taki Demir; Asad Masood; Muhammad Samsam Raza; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Ozhan Simsek; Temoor Ahmed; et al. (Genetic Resources and Crop Evolution, 2026)

Retraction Note: Unveiling the genetic diversity and host specificities of rust: morphological and molecular characterization of Berberis species - Siraj Uddin; Javed Iqbal; Banzeer Ahsan Abbasi; Shumaila Ijaz; Ghulam Murtaza; Muhammad Waseem; Umar Masood Quraishi; Atman Adiba; Reem M. Aljowaie; Saeedah Musaed Almutairi; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Mitigating Chromium-Induced Toxicity in Wheat Using Quantum Dots: Physiological, Biochemical, and Seed Composition Responses in SKD-1 and Borlaug-16 Cultivars - Muhammad Anas; Amjid Khan; Umar Masood Quraishi (Journal of Soil Science and Plant Nutrition, 2026)

Biochar and Montmorillonite in Combination Improved the Plant growth, physiology, Yield and Decreased Lead (Pb) Uptake in Wheat (Triticum aestivum L.) Under Pb Stress - Zaffar Malik; Suliman Mohammed Suliman Alghanem; Nasir Masood; Hina Rizvi; Muhammad Waseem; Ahmad Ali; Haifa Abdul Aziz Sakit Alhaithloul; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2026)

Alleviation of Lead Stress in Maize Plants Through the Application of Green-Synthesized Zinc Oxide Nanoparticles - Haseeba Maryam; Nasir Masood; Muhammad Waseem; Temoor Ahmed; Muhammad Zia-ur-Rehman; Muhammad Atif Irshad; Saher Javed; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2026)

Efficient De Novo Assembly and Recovery of Microbial Genomes from Complex Metagenomes Using a Reduced Set of k-mers - Hajra Qayyum; Muhammad Faheem Raziq; Haseeb Manzoor; Syed Shujaat Ali Zaidi; Amjad Ali; Masood Ur Rehman Kayani (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Disordered Pr-alumina: Enabling fast proton dynamics across energy systems - Hafsa Mansha; Touseef Ahmad; Kashf Zaman; Sajid Rauf; Muhammad Khalid; M.Ahsan Masood; Shahzad Rasool; Atif Nazar; Bushra Bibi; Nawal K. Almaymoni; Yuzheng Lu; Jun Wang; et al. (Fuel, 2026)

In-situ sequential topotactic transformation of ZIF-8 to N-doped Zn-oxide/sulfide with defect engineering for efficient radiocesium capture - Muhammad Ikram; Toshio Yamaguchi; Iltaf Muhammad; Qirui Wang; Hongyan Liu; Shahzad Afzal; Israr Masood ul Hasan; Yongquan Zhou (Chemical Engineering Journal, 2026)

Magnoflorine and its structural diversity: mechanisms, and drug discovery opportunities a review - Muhammad Muzammil Nazir; Ghanva Mustafa; Saira Saeed; Warisha Ghaffar; Iqra Farzeen; Aamir Masood; Asma Ashraf (Molecular Diversity, 2026)

A Snapshot of Brucellosis as an Occupational Health Hazard in Animal Handlers of an Agroecological Zone of Southern Punjab, Pakistan - Abdul Sammad Ali Khan Shirwany; Mian Muhammad Awais; Saad Masood; Aayesha Riaz; Masood Akhtar; Hosny El-Adawy; Faqir Muhammad; Muhammad Irfan Anwar; Mamoona Chaudhry (Journal of Agromedicine, 2026)

Computational prediction of thermomechanical properties in ionic liquid-modified MWCNT/carbon fiber composites - Bilal Ghafoor; Faisal Ghafoor; You Jinglin; Muhammad Shakeel Ahmed; Masood Ahmed; Silvia Tamborim; Sandro Campos Amico; Henri Stephan Schrekker (Next Research, 2026)

Metal organic frameworks derived novel metal sulfide (KCoZnS) nanosheet as an efficient collector for cesium ions - Muhammad Ikram; Hongyan Liu; Iltaf Muhammad; Qirui Wang; Shahzad Afzal; Masood Ul Hasan Israr; Asad Ali; Yongquan Zhou (Journal of Environmental Chemical Engineering, 2025)

Correction: Sepsis-related immune signature C3 in endometrial carcinoma: implications for prognosis, tumor progression through bioinformatics and experimental validation - Kulsoom; Wajahat Ali; Saleem Ahmad; Irfan Ali Khan; Tanveen Kaur Soni; Asia Masood; Muhammad Omer Iqbal; Valisher Sapayev Odilbek uglu; Mukhayya Xusinovna Djumaniyazova; Anas Sameed Cholavaram; Mubaraq Arisekola Abdulrahmon (Molecular Biology Reports, 2025)

Sepsis-related immune signature C3 in endometrial carcinoma: implications for prognosis, tumor progression through bioinformatics and experimental validation - Kulsoom; Wajahat Ali; Saleem Ahmad; Irfan Ali Khan; Tanveen Kaur Soni; Asia Masood; Muhammad Omer Iqbal; Valisher Sapayev Odilbek uglu; Mukhayya Xusinovna Djumaniyazova; Anas Sameed Cholavaram; Mubaraq Arisekola Abdulrahmon (Molecular Biology Reports, 2025)

Green Synthesis of Mangifera Indica Mediated NiO and NiMn2O4 Nanomaterials for Electrocatalytic Water Splitting - Fatima Masood; Shabbir Hussain; Muhammad Arif; Shahzad Murtaza; Muhammad Imran; Muhammad Bilal Tahir; Khurram Shahzad Munawar; Hamad M. Alkahtani; Amer Alhaj Zen; Syed Adnan Ali Shah (International Journal of Environmental Research, 2025)

Impact of Silicon Application on the Mineral Nutrient Profile and Fruit Quality of Mandarin Citrus Hybrid ‘Kinnow’ - Hafiz Faiq Bakhat; Muhammad Imran Razzaq; Muhammad Shafique Khalid; Sunaina Abbas; Natasha; Masood Iqbal Awan; Hasnain Anwar; Ghulam Mustafa Shah; Saira Afzal; Muhammad Rizwan Ashraf; Hafiz Mohkum Hammad (Applied Fruit Science, 2025)

Strategic valorization of heterogeneous organic wastes for sustainable food packaging: A circular economy approach - Shumaila Masood; Hafiz Muhammad Shahbaz; Md. Abdus Salam Shaik; Sajid Maqsood (Trends in Food Science & Technology, 2025)

Photo-activated proton-incorporation into Nd-aluminum for superionic conductors - Atif Nazar; Bushra Bibi; Sajid Rauf; Rizwan Raza; Muhammad Farrukh Sarfraz; Muhammad Khalid; Muhammad Faisal Anwar; Muhammad Ahsan Masood; Kashif Nazar; Syed Asad Abbas Bukhari; Khuloud A. Alibrahim; Bin Zhu; et al. (Chemical Engineering Journal, 2025)

Development of a Novel Composite Catalyst containing Renewable Biochar blended with Zinc Oxide and Copper Diphenyl Amine for Visible Light Photocatalytic Degradation of Methylene Blue - Muhammad Raashid; Muhammad Zain Akram; Mohsin Kazmi; Kashaf Imran; Amir Ikhlaq; Muhammad Bin Saeed; Naveed Ramzan; Zafar Masood (Water, Air, & Soil Pollution, 2025)

Dose–response impact of arsenite on wheat (Triticum aestivum L.) genotypes: unravelling growth, accumulation, and antioxidant modulation for tolerance - Muhammad Saeed; Umar Masood Quraishi; Riffat Naseem Malik (Physiology and Molecular Biology of Plants, 2025)

Antifungal potential of non-ribosomal peptide producing Serratia surfactantfaciens (S31) and Alcaligenes pakistanensis (S33) isolated from the Solanum lycopersicum rhizosphere - Aetsam Bin Masood; Malik Badshah; Muhammad Ishtiaq Ali; Khadija Masood; Asif Jamal; Mogens Nicolaisen (Physiological and Molecular Plant Pathology, 2025)

Advancements in metasurfaces for polarization control: A comprehensive survey - Humayun Zubair Khan; Jamal Zafar; Abdul Jabbar; Jalil ur Rehman Kazim; Masood Ur Rehman; Muhammad Ali Imran; Qammer H. Abbasi (Next Research, 2025)

Non-small Cell Lung Cancer, Immunotherapy and the Influence of Gut Microbiome - Muhammad Faheem Raziq; Haseeb Manzoor; Masood Ur Rehman Kayani (Current Microbiology, 2025)

Impact Assessment of Optimal Water Allocation Using a Linear Model in Lower Bari Doab Canal Command Area - Atiqa Yasin; Muhammad Awais Zafar; Muhammad Masood; Ghulam Nabi; Mudassar Iqbal (Water Conservation Science and Engineering, 2025)

Exploring the antitumor effects of Pd(II) complexes with nitrogen donor ligands towards breast carcinoma - Shazia Hussain; Sara Masood; Shabeeb Hussain; Irfan Hussain; Fouzia Malik; Muhammad Nadeem Akhtar; M. Naveed Zafar (BioMetals, 2025)

Molecular characterization and epidemiological insights into serotypes of foot-and-mouth disease virus in Pakistan - Syeda Anam Masood Gardezi; Masood Rabbani; Muhammad Hassan Mushtaq; Muhammad Zubair Shabbir (Archives of Virology, 2025)

Green-fabricated MnO₂ nanoparticles function as dual nanofertilizers and chromium remediators, enhancing antioxidant pathways, ionomic networks, and physiological resilience in wheat - Muhammad Anas; Umar Masood Quraishi (Journal of Trace Elements in Medicine and Biology, 2025)

Restoring wheat productivity and nutrient balance under cadmium stress through reducing toxicity, metal uptake, and oxidative damage using selenium nanoparticles - Ayesha Jamil Abbasi; Muhammad Anas; Minhas Elahi; Amjid Khan; Waseem Ahmed Khattak; Muhammad Hamzah Saleem; Shah Fahad; Hosam O. Elansary; Eman A. Mahmoud; Temoor Ahmed; Umar Masood Quraishi (Journal of Trace Elements in Medicine and Biology, 2025)

Physiochemical and transcriptomics of exotic holstein friesian cattle in Pakistani subtropics - Masood Ur Rehman; Rajwali Khan; Syed Muhammad Suhail; Iqbal Munir; Khalid Mahmood; Amel Ayari Akari (Tropical Animal Health and Production, 2025)

Exploring the morpho-physiological responses of maize to nickel stress modulated by salicylic acid - Atifa Masood; Sumaira Arooj; Muhammad Shahbaz; Noreen Khalid; Muhammad Sajjad; Muhammad Faisal Maqsood; Sunbal Khalil Chaudhari; Abida Abid; Rafia Zainab; Noor Fatima (Cereal Research Communications, 2025)

Hydrocarbon generation potential of the lower Jurassic-Eocene intervals in the Potwar Plateau, Pakistan: insights from organic geochemical, 1D basin modeling and petrographic analysis - Masood Shah; Syed Mamoon Siyar; Abbas F. Gharib; Iman M. Anwer; Muhammad Irfan; Mohammad Salman Shamim; Nasar Khan; Taqweem Ul. Haq; Yasir Hamid; Kamran Shams (Carbonates and Evaporites, 2025)

The role of nitric oxide and nitrogen in mediating copper stress in Brassica juncea L. - Bilal A. Rather; Asim Masood; Fei Qiao; Xuefei Jiang; Muhammad Mubashar Zafar; Hanqing Cong; Nafees A. Khan (Plant Science, 2025)

Efficacy of ascorbic acid coated quantum dots in alleviating lead-induced oxidative damage and enhancing growth parameters in rice (Oryza sativa L.) for sustainable cultivation - Aliza Falak; Muhammad Anas; Amjid Khan; Alvina Hayat; Zeenat Shaheen; Muhammad Hamzah Saleem; Shah Fahad; Umar Masood Quraishi (Journal of Trace Elements in Medicine and Biology, 2025)

Application of gamma spectrum analysis techniques for natural radioactivity measurements using NaI(Tl) detector - Namra Naeem; Muhammad Sohail; Rizwan Ahmed; Shoaib Masood (Environmental Monitoring and Assessment, 2025)

Unveiling exceptional conduction mechanism and high proton conductivity in amorphous electrolyte for advanced ceramic fuel cells - Touseef Ahmad; Naveed Mushtaq; Hafsa Mansha; Kashf Zaman; Muhammad Khalid; Muhammad Ahsan Masood; Muhammad Shahid Sharif; Yuzheng Lu; Bin Zhu (Fuel, 2025)

Exposure of city-dwellers to particulate matters during commuting trips in the metropolitan area of Karachi - Muhammad Kamran Khan; Haider A. Khwaja; Sumayya Saied; Mirza M. Hussain; Saiyada Shadiah Masood; Rija Zehra (Atmospheric Pollution Research, 2025)

Increasing Salinity and Cadmium Enhanced Leaf Membrane Damage and H2O2 Production Irrespective of Reduced Sodium and Cadmium Accumulation in Wheat (Triticum aestivum L.) - Sajid Masood; Muhammad Ashraf; Mubshar Hussain; M. Farooq Azhar; M. Zafar-ul-Hye; Omer Farooq; Muhammad Aon; M. Tariq Javed (Journal of Soil Science and Plant Nutrition, 2025)

RETRACTED ARTICLE: Unveiling the genetic diversity and host specificities of rust: morphological and molecular characterization of Berberis species - Siraj Uddin; Javed Iqbal; Banzeer Ahsan Abbasi; Shumaila Ijaz; Ghulam Murtaza; Muhammad Waseem; Umar Masood Quraishi; Atman Adiba; Reem M. Aljowaie; Saeedah Musaed Almutairi; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Optimizing callogenesis in five potential medicinal herbs for the bioactive constituents: a sustainable approach to pharmaceutical production - Muhammad Wasim Haider; Muhammad Nafees; Maryyam Bint-e-Tariq; Umar Farooq; Tanveer Hussain; Taki Demir; Asad Masood; Muhammad Samsam Raza; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Ozhan Simsek; Temoor Ahmed; et al. (Genetic Resources and Crop Evolution, 2025)

Mitigating lead (Pb) toxicity in Zea mays (L.) plants using green synthesized iron oxide nanoparticles - Haseeba Maryam; Muhammad Rizwan; Nasir Masood; Muhammad Waseem; Temoor Ahmed; Muhammad Farooq Qayyum; Muhammad Zia-ur-Rehman; Humera Aziz (South African Journal of Botany, 2024)

Adaptive mechanisms of wheat cultivars to lead toxicity through enhanced oxidative defense, ionomic redistribution, and anatomical modifications - Muhammad Anas; Muhammad Saad Bashir; Khadija Saleem; Atika Noor; Umar Masood Quraishi (Journal of Plant Physiology, 2024)

The interplay of PTEN and AKT nexus in breast cancer: a molecular perspective - Anum Kamal; Ali Raza Awan; Masood Rabbani; Hammad Raza Sheikh; Muhammad Tayyab; Sehrish Firyal; Imran H. Khan; Muhammad Wasim (Molecular Biology Reports, 2024)

Performance evaluation of irrigation outlets with physical model study in Indus basin irrigation system of Pakistan - Ghulam Nabi; Fiaz Hussain; Bilal Sajjad; Muhammad Masood; Dengfeng Liu (Environmental Monitoring and Assessment, 2024)

Profusion of microplastics in dental healthcare units; morphological, polymer, and seasonal trends with hazardous consequences for humans - Naseem Akhtar; Arifa Tahir; Abdul Qadir; Rehana Masood; Zain Gulzar; Muhammad Arshad (Journal of Hazardous Materials, 2024)

Evaluating satellite-based precipitation products for spatiotemporal drought analysis - Hussain Masood Khan; Muhammad Fahim Aslam; Muhammad Waseem; Hafiz Kamran Jalil Abbasi; Ali Iftikhar; Faraz Ul Haq (Journal of Arid Environments, 2024)

Anatomical and Ionomics Investigation of Bread Wheat (Triticum aestivum L.) to Decipher Tolerance Mechanisms Under Arsenic Stress - Muhammad Anas; Muhammad Saeed; Kashif Naeem; Munib Ahmed Shafique; Umar Masood Quraishi (Journal of Plant Growth Regulation, 2024)

Evaluating the comprehensive flood impact assessment on the head reach of the Chiniot dam project - Shahzad Yousaf; Zohreh Rajabi; Muhammad Masood; M. Attiqurehman Tariq; Maria Talib; Ahmad Mujtaba (Total Environment Advances, 2024)

Metrics for Sustainability and Circular Economy Practices in Context to Modern Manufacturing Environment - Mohd Bilal Naim Shaikh; Mohammed Ali; Umer Masood Chaudry; Muhammad Kashif Khan (Circular Economy and Sustainability, 2024)

Tailoring structural and optical properties of Cu(II)-induced MgAl2O4 nanoparticles and their response to toxic dyes under solar illumination - Muhammad Javed; Naeem Akbar; Ayaz Arif Khan; Asad Masood; Naeem Ahmed; Muhammad Junaid Khan; Nisar Ahmed; Said Nasir Khisro; Muhammed Ali Shaikh Abdul Hameed (Environmental Science and Pollution Research, 2024)

Enhanced capacity of thiol-functionalized sugarcane bagasse and rice husk biochars for arsenite sorption in aqueous solutions - Israr Masood ul Hasan; Nabeel Khan Niazi; Irshad Bibi; Fazila Younas; Fahad Al-Misned; Muhammad Bilal Shakoor; Fawad Ali; Shazia Ilyas; Muhammad Mahroz Hussain; Jinli Qiao; Andreas Lüttge (Environmental Science and Pollution Research, 2024)
The utilization of biowastes for producing biochar to remove potentially toxic elements from water represents an important pathway for aquatic ecosystem decontamination. Here we explored the significance of thiol-functionalization on sugarcane bagasse biochar (Th/SCB–BC) and rice husk biochar (Th/RH–BC) to enhance arsenite (As(III)) removal capacity from water and compared their efficiency with both pristine biochars (SCB–BC and RH–BC). The maximum As(III) sorption was found on Th/SCB–BC and Th/RH–BC (2.88 and 2.51 mg g −1 , respectively) compared to the SCB–BC and RH–BC (1.51 and 1.40 mg g −1 ). Relatively, a greater percentage of As(III) removal was obtained with Th/SCB–BC and Th/RH–BC (92% and 83%, respectively) at a pH 7 compared to pristine SCB–BC and RH–BC (65% and 55%) at 6 mg L −1 initial As(III) concentration, 2 h contact time and 1 g L −1 sorbent dose. Langmuir ( R 2 = 0.99) isotherm and pseudo-second-order kinetic ( R 2 = 0.99) models provided the best fits to As(III) sorption data. Desorption experiments indicated that the regeneration ability of biochars decreased and it was in the order of Th/SCB–BC (88%) > Th/RH–BC (82%) > SCB–BC (77%) > RH–BC (69%) up to three sorption–desorption cycles. Fourier-transform infrared spectroscopy and X-ray photoelectron spectroscopy results demonstrated that the thiol (-S–H) functional groups were successfully grafted on the surface of two biochars and as such contributed to enhance As(III) removal from water. Spectroscopic data indicated that the surface functional moieties, such as -S–H, − OH, − COOH, and C = O were involved to increase As(III) sorption on thiol-functionalized biochars. This study highlights that thiol-grafting on both biochars, notably on SCB–BC, enhanced their ability to remove As(III) from water, which can be used as an effective technique for the treatment of As from drinking water. Graphical Abstract

Cenchrus ciliaris L. ameliorates cigarette-smoke induced acute lung injury by reducing inflammation and oxidative stress - Muhammad Irfan Aslam; Saad Touqeer; QurratUlAin Jamil; Muhammad Irfan Masood; Adeel Sarfraz; Shafaat Yar Khan; Muhammad Saeed Jan; Sulaiman Mohammed Abdullah Alnasser; Ashfaq Ahmad; Fatima Aslam; Shahid Muhammad Iqbal (South African Journal of Botany, 2024)

Antioxidative enzymes, phytochemicals and proximate components in jujube fruit (Ziziphus mauritiana L.) with respect to genotypes and harvest maturity - Zohaib Asghar; Muhammad Amin; Sami Ullah; Hamad Hassan; Umm-e Habiba; Kashif Razzaq; Ishtiaq Ahmad Rajwana; Gulzar Akhtar; Hafiz Nazar Faried; Muhammad Aiyub; Shafa Nayab; Ambreen Naz; et al. (Food Bioscience, 2024)

Correction to: Hydrologic interpretation of machine learning models for 10-daily streamflow simulation in climate sensitive upper Indus catchments - Haris Mushtaq; Taimoor Akhtar; Muhammad Zia ur Rahman Hashmi; Amjad Masood; Fahad Saeed (Theoretical and Applied Climatology, 2024)

In vitro exploration of Acinetobacter strain (SG-5) for antioxidative potential and phytohormone biosynthesis in maize (Zea mays L.) cultivars differing in cadmium tolerance - Saghir Abbas; Kashif Tanwir; Muhammad Hussaan; Sajid Masood; Qasim Ali; Ali Raza; Muhammad Shahid; Hassan Javed Chaudhary; Saba Mushtaq; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2024)

Modulation of rhizosphere microbial community and metabolites by bio-functionalized nanoscale silicon oxide alleviates cadmium-induced phytotoxicity in bayberry plants - Temoor Ahmed; Linfei Shou; Junning Guo; Muhammad Noman; Yetong Qi; Yanlai Yao; Hafiza Ayesha Masood; Muhammad Rizwan; Md. Arshad Ali; Hayssam M. Ali; Bin Li; Xingjiang Qi (Science of The Total Environment, 2024)

Florfenicol removal from veterinary pharmaceutical effluents: Tri-metallic zeolite 5A° for electrochemical oxidation and catalytic ceramic membrane separation - Amir Ikhlaq; Maryam Gull; Afnan Sajid; Khurram Saleem Joya; Muhammad Raashid; Osama Shaheen Rizvi; Zafar Masood; Salman Ahmed; Maryam Abid; Maham Hanif; Hafiz Abdul Aziz; Thamer Abdulhameed Al Johani; et al. (Journal of Environmental Chemical Engineering, 2024)

Metabolomics profiling reveals the detoxification and tolerance behavior of two bread wheat (Triticum aestivum L.) varieties under arsenate stress - Muhammad Saeed; Umar Masood Quraishi; Ghazala Mustafa; Abida Farooqi; Maria Greger; Riffat Naseem Malik (Food Chemistry, 2024)

Tapping the nutraceutical potential of industrial hemp against arthritis and diabetes - A comprehensive review - Allah Rakha; Hina Rasheed; Ammar B. Altemimi; Sidra Tul-Muntaha; Iraj Fatima; Masood Sadiq Butt; Saddam Hussain; Zuhaib F. Bhat; Amin Mousavi Khaneghah; Rana Muhammad Aadil (Food Bioscience, 2024)

Hydrologic interpretation of machine learning models for 10-daily streamflow simulation in climate sensitive upper Indus catchments - Haris Mushtaq; Taimoor Akhtar; Muhammad Zia ur Rahman Hashmi; Amjad Masood; Fahad Saeed (Theoretical and Applied Climatology, 2024)
Machine learning for hydrologic modeling has seen significant recent development and has been suggested as a valuable augmentation to physical hydrological modeling, especially in data-scarce catchments. In Pakistan, surface water flows predominantly originate from the transboundary Upper Indus sub-catchments of Chenab, Jhelum, Indus, and Kabul rivers. These catchments have large drainage areas, climate-driven streamflows, high variations in elevation, and limited streamflow gauge coverage. Hence, using machine learning models for data-driven river flow modeling may be well-suited for these catchments. However, hydrologic interpretability of machine learning models is important for the practical use of such models for these catchments. Thus, the current study besides evaluating the potential of three machine learning models (XGBOOST, Classification and Regression Trees(CART), and RandomForest) for streamflow simulation also focused on the hydrologic interpretation of machine learning models using SHapley Additive exPlananations (SHAP). All of these models performed well and the range of $$R^2$$ R 2 and Nasche-Efficiency for all three models lies between 0.61 to 0.90. Moreover, SHAP correctly identified minimum temperature as the most critical feature in glacier-fed Indus and Chenab catchments. It also provides logical insights into interactions between minimum temperature and precipitation for the indus and Chenab catchment. The findings of this study strongly illustrate the usefulness of SHAP analysis in interpreting the behavior of data-scarce high-elevation climate-sensitive catchments using tree-based machine learning models.

The therapeutic effect of BODIPY-based photosensitizers against acetylcholinesterase for the treatment of Alzheimer’s disease - Mushtaq Ahmed; Nadia Mushtaq; Naila Sher; Rahmat Ali Khan; Muhammad Amir Masood (Journal of Proteins and Proteomics, 2024)

Generative vs. Non-Generative Models in Engineering Shape Optimization - Zahid Masood; Muhammad Usama; Shahroz Khan; Konstantinos Kostas; Panagiotis D. Kaklis (Journal of Marine Science and Engineering, 2024)
Generative models offer design diversity but tend to be computationally expensive, while non-generative models are computationally cost-effective but produce less diverse and often invalid designs. However, the limitations of non-generative models can be overcome with the introduction of augmented shape signature vectors (SSVs) to represent both geometric and physical information. This recent advancement has inspired a systematic comparison of the effectiveness and efficiency of generative and non-generative models in constructing design spaces for novel and efficient design exploration and shape optimization, which is demonstrated in this work. These models are showcased in airfoil/hydrofoil design, and a comparison of the resulting design spaces is conducted in this work. A conventional generative adversarial network (GAN) and a state-of-the-art generative model, the performance-augmented diverse generative adversarial network (PaDGAN), are juxtaposed with a linear non-generative model based on the coupling of the Karhunen–Loève Expansion and a physics-informed shape signature vector (SSV-KLE). The comparison demonstrates that, with an appropriate shape encoding and a physics-augmented design space, non-generative models have the potential to cost-effectively generate high-performing valid designs with enhanced coverage of the design space. In this work, both approaches were applied to two large foil profile datasets comprising real-world and artificial designs generated through either a profile-generating parametric model or a deep-learning approach. These datasets were further enriched with integral properties of their members’ shapes, as well as physics-informed parameters. The obtained results illustrate that the design spaces constructed by the non-generative model outperform the generative model in terms of design validity, generating robust latent spaces with no or significantly fewer invalid designs when compared to generative models. The performance and diversity of the generated designs were compared to provide further insights about the quality of the resulting spaces. These findings can aid the engineering design community in making informed decisions when constructing design spaces for shape optimization, as it has been demonstrated that, under certain conditions, computationally inexpensive approaches can closely match or even outperform state-of-the art generative models.

Comparative morpho-physiological traits, antioxidant defense and nutritional profiling under Cd stress of japonica-indica elite rice (Oryza sativa L.) cultivars - Alvina Hayat; Muhammad Anas; Zeenat Shaheen; Aliza Falak; Umar Masood Quraishi (Journal of Crop Science and Biotechnology, 2024)

Synthesis and characterizations of conocarpus- and azadirachta-derived activated carbons as wastewater recycling material - Murtuza Mehdi; Mirza Hammad Baig; Masood Ahmad; Kamran Ali; Muhammad Mohib; Ali Farooqi; Mohammad Affan; Muhammad Mazin (Environmental Monitoring and Assessment, 2024)

Efficient treatment of veterinary pharmaceutical industrial wastewater by catalytic ozonation process: degradation of enrofloxacin via molecular ozone reactions - Amir Ikhlaq; Zafar Masood; Umair Yaqub Qazi; Muhammad Raashid; Osama Shaheen Rizvi; Hafiz Abdul Aziz; Muhammad Saad; Fei Qi; Rahat Javaid (Environmental Science and Pollution Research, 2024)

Efficient synergistic degradation of Congo red and omeprazole in wastewater using rGO/Ag@ZnO nanocomposite - Nazish Kousar; Sufian Rasheed; Kousar Yasmeen; Abdul Rehman Umar; Mouna Hind Laiche; Mohsin Masood; Haji Muhammad; Muddasir Hanif (Journal of Water Process Engineering, 2024)

Assessment of nighttime air quality over an urban location in Indo-Gangetic plain using remote sensing observations - Abd Alwahed Dagestani; Salman Tariq; Muhammad Khan; Mustafa Kamal; Masood ur Rehman (Atmospheric Pollution Research, 2024)

Corrigendum to “Evaluation of nanoceria on cadmium uptake in Triticum aestivum (L.) and its implications for dietary health risk” [Chemosphere 341 November (2023) 140115] - Arwa Abdulkreem AL-Huqail; Suliman Mohammed Suliman Alghanem; Zahid Khorshid Abbas; Nora M. Al Aboud; Nasir Masood; Muhammad Atif Irshad; Tahir Abbas; Amany H.A. Abeed; Doaa Bahaa Eldin Darwish (Chemosphere, 2024)

Arsenic accumulation pattern in water-soil-rice systems: A study of tolerance mechanisms and associated health risks - Muhammad Saeed; Muhammad Anas; Umar Masood Quraishi; Riffat Naseem Malik (Science of The Total Environment, 2024)

Phenomic profiling to reveal tolerance mechanisms and regulation of ascorbate–glutathione cycle in wheat varieties (Triticum aestivum L.) under arsenic stress - Muhammad Saeed; Umar Masood Quraishi; Tommy Landberg; Maria Greger; Riffat Naseem Malik (Environmental Geochemistry and Health, 2024)

Biowaste-based sorbents for arsenic removal from aqueous medium and risk assessment - Maham Akhtar Nagra; Natasha Natasha; Irshad Bibi; Tasveer Zahra Tariq; Rabia Naz; Sabah Ansar; Muhammad Shahid; Behzad Murtaza; Muhammad Imran; Muhammad Shafique Khalid; Nasir Masood; Ghulam Mustafa Shah; et al. (Environmental Geochemistry and Health, 2023)

Evaluation of nanoceria on cadmium uptake in Triticum aestivum (L.) and its implications for dietary health risk - Arwa Abdulkreem AL-Huqail; Suliman Mohammed Suliman Alghanem; Zahid Khorshid Abbas; Nora M. Al Aboud; Nasir Masood; Muhammad Atif Irshad; Tahir Abbas; Amany H.A. Abeed; Doaa Bahaa Eldin Darwish (Chemosphere, 2023)

Assessment of rainwater harvesting potential for urban area under climate and land use changes using geo-informatics technology - Saif Haider; Muhammad Umer Masood; Muhammad Rashid; Tauqeer Ali; Chaitanya B. Pande; Fahad Alshehri; Ismail Elkhrachy (Urban Climate, 2023)

Pharmacological and toxicological evaluation of methyl 4-hydroxy-2H-1,2-benzothiazine-3-carboxylate 1,1-dioxoide against haloperidol induced Parkinson like symptoms in animal model: In-vitro and in-vivo studies - Liaqat Hussain; Ina Masood; Matloob Ahmad; Muhammad Yasir Ali; Uzma Saleem; Musaddique Hussain; Syed Haroon Khalid; Zunera Chauhdary (Toxicology and Applied Pharmacology, 2023)

Biogenic silicon nanoparticles mitigate cadmium (Cd) toxicity in rapeseed (Brassica napus L.) by modulating the cellular oxidative stress metabolism and reducing Cd translocation - Temoor Ahmed; Hafiza Ayesha Masood; Muhammad Noman; Arwa Abdulkreem AL-Huqail; Suliman MS Alghanem; Muhammad Munem Khan; Sher Muhammad; Natasha Manzoor; Muhammad Rizwan; Xingjiang Qi; Amany H.A. Abeed; Bin Li (Journal of Hazardous Materials, 2023)

Novel sol–gel synthesis of Mo-doped ZnO-NPs for photo-catalytic waste water treatment using the RhB dye as a model pollutant - Muhammad Sohaib; Tahir Iqbal; Sumera Afsheen; M. B. Tahir; Arslan Masood; Muhammad Rafique; K. N. Riaz; M. A. Sayed; A. F. Abd El-Rehim; Atif Mossad Ali (Environment, Development and Sustainability, 2023)

Mucoadhesive, Fluconazole-Loaded Nanogels Complexed with Sulfhydryl-β-cyclodextrin for Oral Thrush Treatment - Farwa Muskan Khalid; Muhammad Ijaz; Arshad Mahmood; Muhammad Khurram Waqas; Talib Hussain; Mulazim Hussain Asim; Nadeem Ahmad; Shumaila Arshad; Masood Ur Rehman; Imran Nazir (AAPS PharmSciTech, 2023)

Arsenic fractionation and speciation in different textured soils supplied with farmyard manure and accumulation by sunflower under alkaline calcareous conditions - Muhammad Awais Piracha; Muhammad Ashraf; Sher Muhammad Shahzad; Sajid Masood; Naeem Akhtar; Rizwana Kausar; Awais Shakoor (Environmental Science and Pollution Research, 2023)

Why do we waste so much food? Understanding household food waste through a theoretical framework - Lucas Rodrigues Deliberador; Mário Otávio Batalha; Aldara da Silva César; Muhammad Masood Azeem; Jonathan Lee Lane; Pâmella Rodrigues Silva Carrijo (Journal of Cleaner Production, 2023)

Polyoxyethylene Lauryl Ether (Brij-35) and Poloxamer 407–Based Non-ionic Surfactant Vesicles for Dissolution Enhancement of Tacrolimus - Razia Hanif; Muhammad Imran Khan; Asadullah Madni; Muhammad Furqan Akhtar; Muhammad Farhan Sohail; Ammara Saleem; Mubashar Rehman; Sufyan Junaid Usmani; Aslam Khan; Athar Masood (Journal of Pharmaceutical Innovation, 2023)

Enhancing accuracy of extreme learning machine in predicting river flow using improved reptile search algorithm - Rana Muhammad Adnan; Reham R. Mostafa; Hong-Liang Dai; Salim Heddam; Adil Masood; Ozgur Kisi (Stochastic Environmental Research and Risk Assessment, 2023)

Hydrological response under CMIP6 climate projection in Astore River Basin, Pakistan - Zeshan Ali; Mudassar Iqbal; Ihsan Ullah Khan; Muhammad Umer Masood; Muhammad Umer; Muhammad Usama Khan Lodhi; Muhammad Atiq Ur Rehman Tariq (Journal of Mountain Science, 2023)
Climate change strongly influences the available water resources in a watershed due to direct linkage of atmospheric driving forces and changes in watershed hydrological processes. Understanding how these climatic changes affect watershed hydrology is essential for human society and environmental processes. Coupled Model Intercomparison Project phase 6 (CMIP6) dataset of three GCM’s (BCC-CSM2-MR, INM-CM5-0, and MPI-ESM1-2-HR) with resolution of 100 km has been analyzed to examine the projected changes in temperature and precipitation over the Astore catchment during 2020–2070. Bias correction method was used to reduce errors. In this study, statistical significance of trends was performed by using the Man- Kendall test. Sen’s estimator determined the magnitude of the trend on both seasonal and annual scales at Rama Rattu and Astore stations. MPI-ESM1-2-HR showed better results with coefficient of determination (COD) ranging from 0.70–0.74 for precipitation and 0.90–0.92 for maximum and minimum temperature at Astore, Rama, and Rattu followed by INM-CM5-0 and BCC-CSM2-MR. University of British Columbia Watershed model was used to attain the future hydrological series and to analyze the hydrological response of Astore River Basin to climate change. Results revealed that by the end of the 2070s, average annual precipitation is projected to increase up to 26.55% under the SSP1–2.6, 6.91% under SSP2–4.5, and decrease up to 21.62% under the SSP5–8.5. Precipitation also showed considerable variability during summer and winter. The projected temperature showed an increasing trend that may cause melting of glaciers. The projected increase in temperature ranges from - 0.66°C to 0.50°C, 0.9°C to 1.5°C and 1.18°C to 2°C under the scenarios of SSP1–2.6, SSP2–4.5 and SSP5–8.5, respectively. Simulated streamflows presented a slight increase by all scenarios. Maximum streamflow was generated under SSP5–8.5 followed by SSP2–4.5 and SSP1–2.6. The snowmelt and groundwater contributions to streamflow have decreased whereas rainfall and glacier melt components have increased on the other hand. The projected streamflows (2020–2070) compared to the control period (1990–2014) showed a reduction of 3%–11%, 2%–9%, and 1%–7% by SSP1–2.6, SSP2–4.5, and SSP5–8.5, respectively. The results revealed detailed insights into the performance of three GCMs, which can serve as a blueprint for regional policymaking and be expanded upon to establish adaption measures.

Transcriptomic and proteomic profiling reveals toxicity and molecular action mechanisms of bioengineered chitosan‑iron nanocomposites against Xanthomonas oryzae pv. oryzae - Temoor Ahmed; Luqiong Lv; Muhammad Noman; Hafiza Ayesha Masood; Muhammad Rizwan; Munazza Ijaz; Ashraf Atef Hatamleh; Munirah Abdullah Al-Dosary; Hayssam M. Ali; Jianping Chen; Bin Li (Pesticide Biochemistry and Physiology, 2023)

Nitrogen Management Strategies to Improve Crop Performance, Recovery Efficiency and Their Relationship with Physiological Indices in Dry Direct-Seeded Rice - Hafeez ur Rehman; Imran Ali; Fiaz Ali; Masood Iqbal Awan; Abdul Wakeel; Muhammad Farooq; Mubshar Hussain (International Journal of Plant Production, 2023)

Physico-mechanical and petrographic analysis of the Margalla Hill Limestone, Islamabad, Lesser Himalaya, Pakistan - Basit Ali; Mumtaz Ali Khan; Muhammad Hanif; Masood Anwar; Beenish Ali; Mustafa Yar; Ijaz Ahmed (Carbonates and Evaporites, 2023)

Antibiotics induced changes in nitrogen metabolism and antioxidative enzymes in mung bean (Vigna radiata) - Marium Fiaz; Iftikhar Ahmed; Sumara Masood Ul Hassan; Adnan Khan Niazi; Muhammad Fahim Khokhar; Zeshan; Muhammad Ansar Farooq; Muhammad Arshad (Science of The Total Environment, 2023)

Membrane-processed honey samples for pollen characterization with health benefits - Nabila; Mushtaq Ahmad; Ashwaq T. Althobaiti; Wahid Ali; Khansa Masood; Mohamed Fawzy Ramadan; Bisha Chaudhary; Muhammad Zafar; Muhammad Saeed Akhtar; Shazia Sultana; Sasan Zahmatkesh; Tariq Mehmood; et al. (Chemosphere, 2023)

Polymeric Nanogel for Oral Delivery of the Chemotherapeutic Agent: Fabrication and Evaluation Alongside Toxicological Studies and Histopathological Examination - Humaira Sultana; Muhammad Naeem Aamir; Asadullah Madni; Masood ur Rehman; Afifa Shafiq; Jafir Hussain Shirazi; Sidra Hassan; Sumaira (AAPS PharmSciTech, 2023)

Opportunities and constraints for cleaner production policy in the developing world: a case study of Sindh Region, Pakistan - Love Kumar; Sohail Ali Naqvi; Matthew J. Deitch; Muhammad Jibran Khalid; Komal Naeem; Arjmand Qayyum Amjad; Avinash Kumar; Tesfay Gebretsadkan Gebremicael; Masood Arshad (Environment, Development and Sustainability, 2023)

Assessment of aflatoxin M 1 exposure and associated determinants in children from Lahore, Pakistan - Waseela Ashraf; Abdul Rehman; Mansur-ud-Din Ahmad; Masood Rabbani; Muhammad Hassan Mushtaq; Khalida Aamir; Fareeha Akhtar; Jia-Sheng Wang (Food Additives & Contaminants: Part A, 2023)

Recent trends in green synthesis of silver, gold, and zinc oxide nanoparticles and their application in nanosciences and toxicity: a review - Muhammad Musaddiq Shah; Khurshid Ahmad; Bashir Ahmad; Shahid Masood Shah; Hamid Masood; Muhammad Aamir Ramzan Siddique; Rasheed Ahmad (Nanotechnology for Environmental Engineering, 2022)

Impact of climate change on extreme floods under high-end warming scenario RCP8.5 for the Kabul River Basin in Pakistan - Asif Mehmood; Shaofeng Jia; Muhammad Masood; Aifeng Lv; Rashid Mahmood; Wenbin Zhu (Arabian Journal of Geosciences, 2022)

Coupling biochar with microbial inoculants improves maize growth and nutrients acquisition under phosphorous-limited soil - Hafiz Muhammad Rashad Javeed; Rimsha Naeem; Mazhar Ali; Rafi Qamar; Muhammad Aqeel Sarwar; Fahim Nawaz; Atique-ur-Rehman; Muhammad Shehzad; Amjad Farooq; Haseeb-ur-Rehman; Samina Khalid; Khuram Mubeen; et al. (Acta Physiologiae Plantarum, 2022)

CRISPR-Cas9 based stress tolerance: New hope for abiotic stress tolerance in chickpea (Cicer arietinum) - Muhammad Khuram Razzaq; Muhammad Akhter; Ramala Masood Ahmad; Kaiser Latif Cheema; Aiman Hina; Benjamin Karikari; Ghulam Raza; Guangnan Xing; Junyi Gai; Mohsin Khurshid (Molecular Biology Reports, 2022)

Dysregulated expression of microRNAs acts as prognostic and diagnostic biomarkers for glioma patients - Yusrah Masood; Manahil Shal; Muhammad Furqan Shah; Maria Fazal Ul Haq; Mahmmood Akhtar Kayani; Ishrat Mahjabeen (Molecular Genetics and Genomics, 2022)

Assessment of aflatoxin B 1 -lysine adduct in children and its effect on child growth in Lahore, Pakistan - Waseela Ashraf; Abdul Rehman; Mansur-ud-Din Ahmad; Masood Rabbani; Muhammad Hassan Mushtaq; Khalida Aamir; Kathy S. Xue; Jia-Sheng Wang (Food Additives & Contaminants: Part A, 2022)

Impact of spatial and temporal changes in climate on the Kunhar River Watershed, Pakistan - Ghulam Nabi; Muhammad Tayyab; Haseeb Akbar; Muhammad Arfan; Ijaz Ahmad; Muhammad Masood; Aqeela Zahra (Arabian Journal of Geosciences, 2022)

Arsenic-induced oxidative stress in Brassica oleracea: Multivariate and literature data analyses of physiological parameters, applied levels and plant organ type - Natasha; Muhammad Shahid; Sana Khalid; Irshad Bibi; Samina Khalid; Nasir Masood; Saeed Ahmad Qaisrani; Nabeel Khan Niazi; Camille Dumat (Environmental Geochemistry and Health, 2022)

Bio-diesel production of sunflower through sulphur management in a semi-arid subtropical environment - Athar Mahmood; Masood Iqbal Awan; Sana Sadaf; Ahmed Mukhtar; Xiukang Wang; Sajid Fiaz; Sher Aslam Khan; Habib Ali; Faran Muhammad; Zafar Hayat; Farhana Gul; Shah Fahad (Environmental Science and Pollution Research, 2022)

Tocopherol as plant protector: an overview of Tocopherol biosynthesis enzymes and their role as antioxidant and signaling molecules - Essa Ali; Sayed Hussain; Nazim Hussain; Kaleem Ullah Kakar; Jawad Munawar Shah; Syed Hassan Raza Zaidi; Masood Jan; Kewei Zhang; Muhammad Ali Khan; Muhammad Imtiaz (Acta Physiologiae Plantarum, 2022)

The potential of microbes and sulfate in reducing arsenic phytoaccumulation by maize (Zea mays L.) plants - Natasha; Irshad Bibi; Khalid Hussain; Rabia Amen; Israr Masood Ul Hasan; Muhammad Shahid; Safdar Bashir; Nabeel Khan Niazi; Tariq Mehmood; Hafiz Naeem Asghar; Muhammad Farrakh Nawaz; Muhammad Mahroz Hussain; et al. (Environmental Geochemistry and Health, 2021)

Use of multivariate adaptive regression splines for prediction of body weight from body measurements in Marecha (Camelus dromedaries) camels in Pakistan - Cem Tırınk; Ecevit Eyduran; Asim Faraz; Abdul Waheed; Nasir Ali Tauqir; Muhammad Shahid Nabeel; Mohammad Masood Tariq; Irfan Shahzad Sheikh (Tropical Animal Health and Production, 2021)

Metal accumulation potential, human health risks, and yield attributes of hundred bread wheat genotypes on irrigation with municipal and remediated wastewater - Said Akbar; Zeshan Ali; Sadam Hussain; Ashiq Mohammad; Yousaf Riaz; Adnan Shakeel; Ijaz Ahmad; Maria Mussarat; Riffat Naseem Malik; Kiran Yasmin Khan; Muhammad Sohail; Umar Masood Quraishi (Environmental Science and Pollution Research, 2021)

Wind speed pattern data and wind energy potential in Pakistan: current status, challenging platforms and innovative prospects - Hammad Saulat; Muhammad Masood Khan; Muhammad Aslam; Muhammad Chawla; Sikander Rafiq; Faisal Zafar; Muhammad Mahmood Khan; Awais Bokhari; Farrukh Jamil; Abdul Waheed Bhutto; Aqeel Ahmed Bazmi (Environmental Science and Pollution Research, 2021)

Prediction of live body weight based on body measurements in Thalli sheep under tropical conditions of Pakistan using CART and MARS - Asim Faraz; Cem Tirink; Ecevit Eyduran; Abdul Waheed; Nasir Ali Tauqir; Muhammad Shahid Nabeel; Mohammad Masood Tariq (Tropical Animal Health and Production, 2021)

A comparative analysis of attabad landslide on january 4, 2010, using two numerical models - Hasnain Gardezi; Muhammad Bilal; Qiangong Cheng; Aiguo Xing; Yu Zhuang; Tahir Masood (Natural Hazards, 2021)

Disintegration of uncertainties associated with real-time multi-satellite precipitation products in diverse topographic and climatic area in Pakistan - Muhammad Masood; Ghulam Nabi; Muhammad Babur; Aftab Hussain Azhar; Muhammad Kaleem Ullah (Journal of Mountain Science, 2021)

Machine Learning Outcome Prediction in Dilated Cardiomyopathy Using Regional Left Ventricular Multiparametric Strain - Robert M. MacGregor; Aixia Guo; Muhammad F. Masood; Brian P. Cupps; Gregory A. Ewald; Michael K. Pasque; Randi Foraker (Annals of Biomedical Engineering, 2021)

Correlation of MSH2 exonic deletions and protein downregulation with breast cancer biomarkers and outcome in Pakistani women/patients - Saima Shakil Malik; Sumaira Mubarik; Ayesha Aftab; Ranjha Khan; Nosheen Masood; Muhammad Asif; Razia Bano (Environmental Science and Pollution Research, 2021)

Plant growth-promoting Bacillus sp. strain SDA-4 confers Cd tolerance by physio-biochemical improvements, better nutrient acquisition and diminished Cd uptake in Spinacia oleracea L. - Muhammad Shahid; Muhammad Tariq Javed; Kashif Tanwir; Muhammad Sohail Akram; Syeda Khola Tazeen; Muhammad Hamzah Saleem; Sajid Masood; Sadia Mujtaba; Hassan Javed Chaudhary (Physiology and Molecular Biology of Plants, 2020)

Comparative Response of Two Rice (Oryza sativa L.) Cultivars to Applied Zinc and Manganese for Mitigation of Salt Stress - Faisal Nadeem; Muhammad Azhar; Muhammad Anwar-ul-Haq; Muhammad Sabir; Tayyaba Samreen; Abdullah Tufail; Hafiz Umair Masood Awan; Wu Juan (Journal of Soil Science and Plant Nutrition, 2020)

Dechlorane Plus as an emerging environmental pollutant in Asia: a review - Mazhar Iqbal Zafar; Sundas Kali; Mehtabidah Ali; Muhammad Asam Riaz; Tayyaba Naz; Muhammad Mazhar Iqbal; Noshin Masood; Kashif Munawar; Bilal Jan; Sohail Ahmed; Amir Waseem; Muhammad Bilal Khan Niazi (Environmental Science and Pollution Research, 2020)

Comparative efficacy of mitigation techniques for the detoxification of Prunus persica (L.) from selected pesticide residues - Neelab; Muhammad Rafique Asi; Sundas Kali; Muhammad Asam Riaz; Amir Waseem; Muhammad Mazhar Iqbal; Nauman Ahmad; Mazhar Iqbal; Noshin Masood; Mazhar Iqbal Zafar (Environmental Science and Pollution Research, 2020)

Using GIS tools to detect the land use/land cover changes during forty years in Lodhran District of Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Waseem Akram; Hafiz Mohkum Hammad; Mazhar Ali; Nasir Masood; Asad Amin; Hafiz Umar Farid; Syeda Refat Sultana; Shah Fahad; Depeng Wang; et al. (Environmental Science and Pollution Research, 2020)

Assessment of Real Time, Multi-Satellite Precipitation Products under Diverse Climatic and Topographic Conditions - Muhammad Masood; Abdul Sattar Shakir; Aftab Hussain Azhar; Guhlam Nabi; Habib-u-Rehman (Asia-Pacific Journal of Atmospheric Sciences, 2020)

Examining the impacts of future land use/land cover changes on climate in Punjab province, Pakistan: implications for environmental sustainability and economic growth - Abdus Samie; Azhar Abbas; Muhammad Masood Azeem; Sidra Hamid; Muhammad Amjed Iqbal; Shaikh Shamim Hasan; Xiangzheng Deng (Environmental Science and Pollution Research, 2020)

Single or Combined Applications of Zinc and Multi-strain Probiotic on Intestinal Histomorphology of Broilers Under Cyclic Heat Stress - Muqader Shah; Hafsa Zaneb; Saima Masood; Rifat Ullah Khan; Muhammad Mobashar; Imad Khan; Salahud Din; Muhammad Shoaib Khan; Habib Ur Rehman; Antonella Tinelli (Probiotics and Antimicrobial Proteins, 2020)

Spicing up gastrointestinal health with dietary essential oils - Mahwish Tanveer; Charles Wagner; Muhammad Ikram ul Haq; Nilton C. Ribeiro; Thriumurugan Rathinasabapathy; Masood Sadiq Butt; Aamir Shehzad; Slavko Komarnytsky (Phytochemistry Reviews, 2020)

Correlation of MLH1 polymorphisms, survival statistics, in silico assessment and gene downregulation with clinical outcomes among breast cancer cases - Saima Shakil Malik; Ayisha Zia; Sumaira Mubarik; Nosheen Masood; Sajid Rashid; Alice Sherrard; Muhammad Bilal Khan; Muhammad Tahir Khadim (Molecular Biology Reports, 2020)

Photoperiodic stress induces genotype-specific shift in DNA methylation in Tartary buckwheat - Muhammad Saad; Helen Mary; Umar Amjid; Ghulam Shabir; Kashif Aslam; Shahid Masood Shah; Abdul Rehman Khan (Biologia Futura, 2019)
Tartary buckwheat, known for its rich source of health beneficial secondary metabolites, is cultivated in many areas of the world. Among different environmental factors, photoperiod strongly influence its growth, flowering time, and ultimately the yield. In this context, epigenetics could contribute significantly in the regulation of plant response against changing environment. Therefore, with the aim to study the involvement of DNA methylation in photoperiod mediated plant response, genome-wide DNA methylation analysis was performed in two accessions (A1 and A2) of Tartary buckwheat using three photoperiodic treatments, i.e., 10-hr light/day (T1), 12-hr light/day (T2), and 14-hr light/day (T3). Flowering time and plant fresh weight data revealed that accessions A1 and A2 prefer T1 and T2 treatments, respectively. Total DNA methylation ratio increased with the increase in photoperiod in accession A1 but decreased under same conditions in accession A2. Full methylation increased significantly while intensive decrease in hemimethylation was noted from T2 to T3 in A1, whereas full methylation strongly increased and hemimethylation strongly decreased from T1 to T2 in A2. Overall, the DNA methylation events appeared more frequently than demethylation events. This study reports for the first time an accession-/genotype specific pattern of shift in the DNA methylation under different photoperiodic treatments that will pave the way toward identification of specific genes involved in the regulation of plant response against photoperiodic stress.

Nanocarrier-mediated co-delivery systems for lung cancer therapy: recent developments and prospects - Muhammad Asim Farooq; Md Aquib; Daulat Haleem Khan; Sana Ghayas; Anam Ahsan; Muhammad Ijaz; Parikshit Banerjee; Maqsood Ahmed Khan; Muhammad Masood Ahmad; Bo Wang (Environmental Chemistry Letters, 2019)

Recent advances in the delivery of disulfiram: a critical analysis of promising approaches to improve its pharmacokinetic profile and anticancer efficacy - Muhammad Asim Farooq; Md Aquib; Daulat Haleem Khan; Zahid Hussain; Anam Ahsan; Mirza Muhammad Faran Ashraf Baig; Dickson Pius Wande; Muhammad Masood Ahmad; Hafiz Muhammad Ahsan; Jiang Jiajie; Bo Wang (DARU Journal of Pharmaceutical Sciences, 2019)

First detection and molecular characterization of avian polyomavirus in young parrots in Pakistan - Aayesha Riaz; Arfan Yousaf; Muhammad Moaeen-ud-Din; Muhammad Ali Abdullah Shah; Tayyaba Zainab; Sadia Masood; Naeem Akhter; Adnan Ali (Veterinary Research Communications, 2019)

Economics of death and dying: a critical evaluation of environmental damages and healthcare reforms across the globe - Rubeena Batool; Khalid Zaman; Muhammad Adnan Khurshid; Salman Masood Sheikh; Alamzeb Aamir; Alaa Mohamd Shoukry; Mohamed A. Sharkawy; Fares Aldeek; Jameel Khader; Showkat Gani (Environmental Science and Pollution Research, 2019)

Recombinant Tk0522, a carbohydrate esterase homologue from Thermococcus kodakarensis, does not require a signal sequence for translocation to periplasmic space in Escherichia coli - Anam Tariq; Alina Gul; Majida A. Muhammad; Naeem Rashid; Masood A Siddiqui (Biologia, 2019)

Amelioration of toxicopathological effects of cadmium with silymarin and milk thistle in male Japanese quail (Coturnix japonica) - Muhammad Kashif Saleemi; Muhammad Waseem Tahir; Rao Zahid Abbas; Masood Akhtar; Aamir Ali; Muhammad Tariq Javed; Zahida Fatima; Muhammad Zubair; Sheraz Ahmed Bhatti; Zahoor Ul Hassan (Environmental Science and Pollution Research, 2019)

An insight into clinical outcome of XPG polymorphisms in breast cancer - Saima Shakil Malik; Sumaira Mubarik; Nosheen Masood; Muhammad Tahir Khadim (Molecular Biology Reports, 2018)

Regolith thickness modeling using a GIS approach for landslide distribution analysis, NW Himalayas - Muhammad Basharat; Masood Qasim; Muhammad Shafique; Nasir Hameed; Muhammad Tayyib Riaz; Muhammad Rustam Khan (Journal of Mountain Science, 2018)

The Small Matter of a Red Ox, a Particularly Sensitive Pink Cat, and the Quest for the Yellow Stone of Wisdom - Muhammad Jawad Nasim; Polina Denezhkin; Muhammad Sarfraz; Roman Leontiev; Yannik Ney; Ammar Kharma; Sharoon Griffin; Muhammad Irfan Masood; Claus Jacob (Current Pharmacology Reports, 2018)

Resistance in field populations of Amrasca devastans (Hemiptera: Cicadellidae) to new insecticides in Southern Punjab, Pakistan - Nasir Abbas; Naeem Abbas; Masood Ejaz; Sarfraz Ali Shad; Iqra Asghar; Aima Irum; Muhammad Binyameen (Phytoparasitica, 2018)

Assessment of field evolved resistance to some broad-spectrum insecticides in cotton jassid, Amrasca devastans from southern Punjab, Pakistan - Nasir Abbas; Muhammad Ismail; Masood Ejaz; Iqra Asghar; Aima Irum; Sarfraz Ali Shad; Muhammad Binyameen (Phytoparasitica, 2018)

Resveratrol as an anti-cancer agent: A review - Abdur Rauf; Muhammad Imran; Masood Sadiq Butt; Muhammad Nadeem; Dennis G. Peters; Mohammad S. Mubarak (Critical Reviews in Food Science and Nutrition, 2018)

Therapeutic potential of dairy bioactive peptides: A contemporary perspective - Saira Sultan; Nuzhat Huma; Masood Sadiq Butt; Muhammad Aleem; Munawar Abbas (Critical Reviews in Food Science and Nutrition, 2018)

Evaluation of immunostimulatory and immunotherapeutic effects of tropical mushroom (Lentinus edodes) against eimeriasis in chicken - Muhammad Irfan Ullah; Masood Akhtar; Mian Muhammad Awais; Muhammad Irfan Anwar; Kashfa Khaliq (Tropical Animal Health and Production, 2018)

Pcal_0632, a phosphorylating glyceraldehyde-3-phosphate dehydrogenase from Pyrobaculum calidifontis - Iram Aziz; Naeem Rashid; Raza Ashraf; Masood Ahmed Siddiqui; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2018)

Rice bran nutraceutics: A comprehensive review - Muhammad Sohail; Allah Rakha; Masood Sadiq Butt; Muhammad Jawad Iqbal; Summer Rashid (Critical Reviews in Food Science and Nutrition, 2017)

Assessing the combined toxicity of conventional and newer insecticides on the cotton mealybug Phenacoccus solenopsis - Bushra Saddiq; Masood Ejaz; Sarfraz Ali Shad; Muhammad Aslam (Ecotoxicology, 2017)

Chemical speciation and bioavailability of rare earth elements (REEs) in the ecosystem: a review - Aysha Masood Khan; Nor Kartini Abu Bakar; Ahmad Farid Abu Bakar; Muhammad Aqeel Ashraf (Environmental Science and Pollution Research, 2017)

Comparison of dynamic behaviours of retrofitted and unretrofitted cob material walls - Muhammad Masood Rafi; Sarosh Hashmat Lodi (Bulletin of Earthquake Engineering, 2017)

Evaluation of short-term health effects among rural women and reduction in household air pollution due to improved cooking stoves: quasi experimental study - Tanzil Jamali; Zafar Fatmi; Afshan Shahid; Aneeta Khoso; Muhammad Masood Kadir; Nalini Sathiakumar (Air Quality, Atmosphere & Health, 2017)

Biology and management of Avena fatua and Avena ludoviciana: two noxious weed species of agro-ecosystems - Ali Ahsan Bajwa; Muhammad Javaid Akhter; Nadeem Iqbal; Arslan Masood Peerzada; Zarka Hanif; Sudheesh Manalil; Saima Hashim; Hafiz Haider Ali; Lynda Kebaso; David Frimpong; Halima Namubiru; Bhagirath Singh Chauhan (Environmental Science and Pollution Research, 2017)

Retraction Note to: Release, deposition and elimination of radiocesium (137Cs) in the terrestrial environment - Muhammad Aqeel Ashraf; Ayesha Masood Khan; Mushtaq Ahmad; Shatirah Akib; Khaled S. Balkhair; Nor Kartini Abu Bakar (Environmental Geochemistry and Health, 2017)

Identification of a novel copper-activated and halide-tolerant laccase in Geobacillus thermopakistaniensis - Saadia Basheer; Naeem Rashid; Raza Ashraf; Muhammad Sohail Akram; Masood Ahmed Siddiqui; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2017)

Microelectrophoretic study of environmentally induced DNA damage in fish and its use for early toxicity screening of freshwater bodies - Bilal Hussain; Tayyaba Sultana; Salma Sultana; K. A. Al-Ghanim; Shahreef Masood; Muhammad Ali; Shahid Mahboob (Environmental Monitoring and Assessment, 2017)

TK1656, an L-asparaginase from Thermococcus kodakarensis, a novel candidate for therapeutic applications - Shahid Mahmood Chohan; Muhammad Atif Nisar; Naeem Rashid; Ghazaleh Gharib; Qamar Bashir; Masood Ahmed Siddiqui (Biologia, 2016)

Genetic diversity analysis of Pakistan rice (Oryza sativa) germplasm using multiplexed single nucleotide polymorphism markers - Shahid Masood Shah; Muhammad Arif; Kashif Aslam; Ghulam Shabir; Michael J. Thomson (Genetic Resources and Crop Evolution, 2016)

Co-occurrence of arsenic and fluoride in the groundwater of Punjab, Pakistan: source discrimination and health risk assessment - Atta Rasool; Tangfu Xiao; Zenab Tariq Baig; Sajid Masood; Khan M. G. Mostofa; Muhammad Iqbal (Environmental Science and Pollution Research, 2015)

Tomato ( Solanum lycopersicum ) Carotenoids and Lycopenes Chemistry; Metabolism, Absorption, Nutrition, and Allied Health Claims—A Comprehensive Review - Rashida Perveen; Hafiz Ansar Rasul Suleria; Faqir Muhammad Anjum; Masood Sadiq Butt; Imran Pasha; Sarfraz Ahmad (Critical Reviews in Food Science and Nutrition, 2015)

Differential effects of cadmium and chromium on growth, photosynthetic activity, and metal uptake of Linum usitatissimum in association with Glomus intraradices - Amna; Naeem Ali; Sajid Masood; Tehmeena Mukhtar; Muhammad Aqeel Kamran; Mazhar Rafique; M. Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Monitoring and Assessment, 2015)

Observed damages in Pakistan due to 16 April 2013 Iran earthquake - Muhammad Masood Rafi; Sarosh H. Lodi; Muhammad Ahmed; Naveed Alam (Bulletin of Earthquake Engineering, 2015)

Protein–Energy Malnutrition: A Risk Factor for Various Ailments - Rizwana Batool; Masood Sadiq Butt; Muhammad Tauseef Sultan; Farhan Saeed; Rabia Naz (Critical Reviews in Food Science and Nutrition, 2015)

Onion: Nature Protection Against Physiological Threats - Hafiz Ansar Rasul Suleria; Masood Sadiq Butt; Faqir Muhammad Anjum; Farhan Saeed; Nauman Khalid (Critical Reviews in Food Science and Nutrition, 2015)

Effect of oxytocin on serum biochemistry, liver enzymes, and metabolic hormones in lactating Nili Ravi buffaloes - Zafar Iqbal; Zia ur Rahman; Faqir Muhammad; Masood Akhtar; Mian Muhammad Awais; Tanweer Khaliq; Amar Nasir; Muhammad Nadeem; Kinza Khan; Hafiz Muhammad Arshad; Muhammad Abdul Basit (Tropical Animal Health and Production, 2015)

RETRACTED ARTICLE: Release, deposition and elimination of radiocesium (137Cs) in the terrestrial environment - Muhammad Aqeel Ashraf; Ayesha Masood Khan; Mushtaq Ahmad; Shatirah Akib; Khaled S. Balkhair; Nor Kartini Abu Bakar (Environmental Geochemistry and Health, 2014)

Synthesis, molecular docking and antiviral screening of novel N′-substitutedbenzylidene-2-(4-methyl-5,5-dioxido-3-phenylbenzo[e]pyrazolo[4,3-c][1,2]thiazin-1(4H)-yl)acetohydrazides - Sana Aslam; Matloob Ahmad; Muhammad Makshoof Athar; Usman Ali Ashfaq; John M. Gardiner; Catherine Montero; Mervi Detorio; Masood Parvez; Raymond F. Schinazi (Medicinal Chemistry Research, 2014)

Influence of plant species and phosphorus amendments on metal speciation and bioavailability in a smelter impacted soil: a case study of food-chain contamination - Muhammad Shahid; Tiantian Xiong; Nasir Masood; Tibo Leveque; Katelle Quenea; Annabelle Austruy; Yann Foucault; Camille Dumat (Journal of Soils and Sediments, 2014)

Rice Bran: A Novel Functional Ingredient - Mian Kamran Sharif; Masood Sadiq Butt; Faqir Muhammad Anjum; Saima Hafiz Khan (Critical Reviews in Food Science and Nutrition, 2014)

Black Pepper and Health Claims: A Comprehensive Treatise - Masood Sadiq Butt; Imran Pasha; Muhammad Tauseef Sultan; Muhammad Atif Randhawa; Farhan Saeed; Waqas Ahmed (Critical Reviews in Food Science and Nutrition, 2013)

Aflatoxins: Biosynthesis, Occurrence, Toxicity, and Remedies - Muhammad Abrar; Faqir Muhammad Anjum; Masood Sadiq Butt; Imran Pasha; Muhammad Atif Randhawa; Farhan Saeed; Khalid Waqas (Critical Reviews in Food Science and Nutrition, 2013)

Development of geomorphologic instantaneous unit hydrograph for a large watershed - Abdul Razzaq Ghumman; Muhammad Masood Ahmad; Hashim Nisar Hashmi; Mumtaz Ahmad Kamal (Environmental Monitoring and Assessment, 2012)

Assessment of flood hazard, vulnerability and risk of mid-eastern Dhaka using DEM and 1D hydrodynamic model - Muhammad Masood; Kuniyoshi Takeuchi (Natural Hazards, 2012)

Seasonal prevalence of coccidiosis in industrial broiler chickens in Faisalabad, Punjab, Pakistan - Mian Muhammad Awais; Masood Akhtar; Zafar Iqbal; Faqir Muhammad; Muhammad Irfan Anwar (Tropical Animal Health and Production, 2012)

Estimation of a Unique Pair of Nash Model Parameters: An Optimization Approach - Muhammad Masood Ahmad; Abdul Razzaq Ghumman; Sajjad Ahmad; Hashim Nisar Hashmi (Water Resources Management, 2010)

Nigella sativa : Reduces the Risk of Various Maladies - Masood Sadiq Butt; Muhammad Tauseef Sultan (Critical Reviews in Food Science and Nutrition, 2010)

Effect of induced pyrexia on the disposition kinetics of ciprofloxacin in dogs - Faqir Muhammad; Masood Akhtar; M. Irfan Anwar; M. Javed Arshed (Veterinary Research Communications, 2009)

Estimation of Clark’s Instantaneous Unit Hydrograph Parameters and Development of Direct Surface Runoff Hydrograph - Muhammad Masood Ahmad; Abdul Razzaq Ghumman; Sajjad Ahmad (Water Resources Management, 2009)

Garlic: Nature's Protection Against Physiological Threats - Masood Sadiq Butt; Muhammad Tauseef Sultan; Mehmood S. Butt; Javaid Iqbal (Critical Reviews in Food Science and Nutrition, 2009)

Green Tea: Nature's Defense against Malignancies - Masood Sadiq Butt; Muhammad Tauseef Sultan (Critical Reviews in Food Science and Nutrition, 2009)